Photosynthetic responses of young cashew plants to varying environmental conditions - de Souza, Rogéria Pereira; Ribeiro, Rafael Vasconcelos; Machado, Eduardo Caruso; de Oliveira, Ricardo Ferraz; da Silveira, Joaquim Albenísio Gomes (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The aim of this study was to characterize gas exchange responses of young cashew plants to varying photosynthetic photon flux density (PPFD), temperature, vapor-pressure deficit (VPD), and intercellular CO2 concentration (Ci), under controlled conditions. Daily courses of gas exchange and chlorophyll a fluorescence parameters were measured under natural conditions. Maximum CO2 assimilation rates, under optimal controlled conditions, were about 13 mmol m-2 s-1, with light saturation around 1,000 mmol m-2 s-1. Leaf temperatures between 25oC and 35oC were optimal for photosynthesis. Stomata showed sensitivity to CO2, and a closing response with increasing Ci. Increasing VPD had a small effect on CO2 assimilation rates, with a small decrease above 2.5 kPa. Stomata, however, were strongly affected by VPD, exhibiting gradual closure above 1.5 kPa. The reduced stomatal conductances at high VPD were efficient in restricting water losses by transpiration, demonstrating the species adaptability to dry environments. Under natural irradiance, CO2 assimilation rates were saturated in early morning, following thereafter the PPFD changes. Transient Fv/Fm decreases were registered around 11h, indicating the occurrence of photoinhibition. Decreases of excitation capture efficiency, decreases of effective quantum yield of photosystem II, and increases in non-photochemical quenching were consistent with the occurrence of photoprotection under excessive irradiance levels.